O discurso do poder provincial e a construção da educação feminina no Espírito Santo (1845-1889): entre conhecimentos consentidos e saberes negados - Guisso, Luana Frigulha (2020)
The research aims to understand how female access to schooling occurred in the Province of Espírito Santo between 1845, when the first school for girls appeared in the provincial capital, and the year 1889, when a new phase in Brazilian history began - th